Study on Mechanical Properties and Microstructure of Lightweight High-Toughness Ultra-High Performance Concrete - Taylor, Mark; Ahmad, Kerry; Eastwood, David (Journal of Green Energy and Environmental Engineering, 2026)
Lightweight modification of Ultra-High Performance Concrete (UHPC) represents a key pathway for its sustainable development. This study prepared Lightweight UHPC (LUHPC) by synergistically incorporating hollow glass microspheres (HGM) and fly ash cenospheres (FAC) as replacements for cement and quartz sand. The effects of lightweight modification on macroscopic mechanical properties were systematically evaluated by comparing the compressive strength, axial tensile performance, and apparent density of reference and lightweight specimens, complemented by microstructural analysis to reveal the evolution of hydration products and interfacial transition zone characteristics. Incorporating lightweight components successfully reduced the density of LUHPC by 497.2 kg/m³ while retaining a high compressive strength of 146.6 MPa. Although the tensile strength (9.7 MPa) is marginally lower than that of conventional UHPC (11.2 MPa), the material exhibits distinct strain-hardening behavior, demonstrating excellent tensile ductility. In LUHPC, the pozzolanic activity of fly ash cenospheres consumed more Ca(OH)₂ during hydration, generating C-S-H gel with a low calcium-to-silicon (Ca/Si) ratio and a higher degree of hydration. Hollow glass microspheres improved particle packing and optimized the interfacial structure. The synergistic effect of these two components yielded a denser matrix microstructure, demonstrating superior strength-density compatibility.